2018
DOI: 10.1002/aenm.201803135
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Saturation‐Current Density to Realize High‐Efficiency Low‐Bandgap Mixed Tin–Lead Halide Perovskite Solar Cells

Abstract: The unsatisfactory performance of low‐bandgap mixed tin (Sn)–lead (Pb) halide perovskite subcells has been one of the major obstacles hindering the progress of the power conversion efficiencies (PCEs) of all‐perovskite tandem solar cells. By analyzing dark‐current density and distribution, it is identified that charge recombination at grain boundaries is a key factor limiting the performance of low‐bandgap mixed Sn–Pb halide perovskite subcells. It is further found that bromine (Br) incorporation can effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

19
282
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 287 publications
(314 citation statements)
references
References 42 publications
19
282
0
1
Order By: Relevance
“…Many efforts have been devoted to improving the PCE of low‐bandgap mixed Pb–Sn PSCs . However, it often exhibits a larger open‐circuit voltage ( V oc ) loss, and therefore, its efficiency is far behind that of pure Pb‐based PSCs with a medium bandgap.…”
mentioning
confidence: 99%
“…Many efforts have been devoted to improving the PCE of low‐bandgap mixed Pb–Sn PSCs . However, it often exhibits a larger open‐circuit voltage ( V oc ) loss, and therefore, its efficiency is far behind that of pure Pb‐based PSCs with a medium bandgap.…”
mentioning
confidence: 99%
“…Making use of the large columnar LBG perovskite grains produced by VAGC in this work, PSCs with PCE as high as 18.2% are demonstrated, exceeding the 15.4% of reference devices prepared by the established antisolvent method (Figure 1d). It should be noted that, to date, this represents one of the highest PCEs of the LBG PSC based on pure iodine halogen without incorporation of Br − , [28] Cl − [31] nor incorporation of additives such as GuaSCN. The long-term MPP tracking of the prepared devices by VAGC and the antisolvent method shows similar photo-stability for PSC prepared by VAGC compared to the antisolvent method ( Figure S1, Supporting Information) for devices stored at 25 °C in N 2 atmosphere.…”
mentioning
confidence: 91%
“…[24][25][26][27] While it was shown that these small grains (accompanied by a large number of grain boundaries in the film) do not cause severe problems in Pb-based perovskite thin films, they are reported to be detrimental in Sn-based perovskite thin films [24][25][26][27] due to lots of defects at the grain-boundaries. [28] In perovskite thin films, grain boundaries are known as being potential sites for nonradiative recombination of charge carriers. To further improve the morphology and crystal quality of LBG perovskite thin films, several studies investigated the ratio of halogens in the LBG perovskite thin films.…”
mentioning
confidence: 99%
See 2 more Smart Citations